COMPARISON OF TWO BACKGROUNDS ON 14C ACTIVITY MEASUREMENT WITH LSC (LIQUID SCINTILLATION COUNTING) - Andi Tenrisa’na; Alfian Noor; Muhammad Zakir (Marina Chimica Acta, 2018)
Comparison of the two types of background on 14C activity measurement has been carried out. This study aims to determine a better background for 14C activity measurement using the LSC (Liquid Scintillation Counting) method. The background used consists of two, namely background I and background II. Background I is a marble solution that has been absorbed using 30% DEA. Background II is a 30% DEA solution. Activity measurement of 14C was carried out using Hidex 300 SL liquid scintillation counter (LSC). Activity 14C background I is 99,389 DPM. While Activity 14C background II is 101,178 DPM. This shows that the background that is better used for measuring Activity 14C is background I, which is a marble solution that has been absorbed using DEA